SHORT 2D ANIMATION FOR INCREASING DEPRESSION AWARENESS - Deli Deli; Winna Winna (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Depression is a mental health disorder that affects a person’s mood which is characterized by sadness, hopelessness, stressed and loss of interest in doing any activity. This condition has a very negative impact on a person thoughts, feelings and mental health. Although depression is a mental health disorder that can be treated, unfortunately there is very little public awareness to recognize the symptoms of depression. Which causes a lot of people ignoring depression and leaving it without treatment or consultation with experts. Untreated depression can be life threatening. The number of deaths due to suicide each year can reach 800,000 to 1,000,000 victims and 80% of these deaths are caused by depression. The high mortality rate due to depression reflects the low public awareness of mental health disorders. With this problem, the author wants to increase public awareness and concern for depression through a 2D animated video. In designing this 2D animation, the author uses some software assistance, namely Procreate and Capcut. By using the Multimedia Cycle Development (MDLC) method to assist the animation design process as well as data collection techniques by conducting interviews and literature studies. The final result of this research is a 2D animation with a duration of 2 minutes and 49 seconds with the title "Candle: A Short Animation About Depression" which is distributed to the public through the Youtube platform.